2017
DOI: 10.1155/2017/6971916
|View full text |Cite
|
Sign up to set email alerts
|

The Hazard Content of Cadmium, Lead, and Other Trace Elements in Some Medicinal Herbs and Their Water Infusions

Abstract: 54 samples belonging to 23 herbal species (15 individuals and 8 mixtures) were analyzed for their contents of heavy metals in the raw materials and in their water infusions. Trace and toxic elements in these samples were determined by using inductively coupled plasma-atomic emission spectrometry (ICP-OES) following acid digestion. The order of decreasing mean metal concentrations in raw materials (mg/kg) was found to be as follows: Fe (440) > Mn (162) > Zn (45.8) > Cu (12) > Pb (10.4) > Ni (5.4) > Cr (2.9) > C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
2
12
1
2
Order By: Relevance
“…Our ndings for The range of cadmium in plants from the same sampling region was often broad with maximum and minimum concentrations approximately 12-fold in Manga sub-county and 11-fold in Borabu sub-county. Our ndings are similar to those reported for vegetation and indicated that the vegetation absorbed Cd from contaminated soil and water(Khattak and Khattak 2011;Khan 2013;Ting et al 2013;Zhu et al 2013;Filipiak-Szok et al 2015;Ababneh 2017).…”
supporting
confidence: 91%
“…Our ndings for The range of cadmium in plants from the same sampling region was often broad with maximum and minimum concentrations approximately 12-fold in Manga sub-county and 11-fold in Borabu sub-county. Our ndings are similar to those reported for vegetation and indicated that the vegetation absorbed Cd from contaminated soil and water(Khattak and Khattak 2011;Khan 2013;Ting et al 2013;Zhu et al 2013;Filipiak-Szok et al 2015;Ababneh 2017).…”
supporting
confidence: 91%
“…Sources of heavy metal contamination in herbal preparations could be linked to water used in irrigation, polluted soils, fertilizers and pesticides, industrial emissions, transportation, and harvesting and storage processes [3,4]. Metals such as zinc, iron, manganese, and copper are essential elements since they play an important role in biological systems and only become harmful at high concentrations, whereas mercury, lead, arsenic, chromium, and cadmium are nonessential elements as they are toxic, even at low concentration levels [5]. In general, the toxicity of heavy metals is due to the chemical reactivity of the ions with cellular structural proteins, enzymes, and membrane systems [6].…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, têm ocorrido uma crescente preocupação no meio científico com a segurança e a qualidade (Zeiner & Cindrić, 2017) inerente à toxicidade de metais pesados em medicamentos à base de plantas, e isso é ilustrado pelos vários estudos realizados em países Asiáticos, como a China (Kong et al, 2020;Luo et al, 2021;Meng et al, 2021), Paquistão (Khan et al, 2021), Índia (Subramanian et al, 2012) e Filipinas (Solidum, 2014), em países Africanos, como Etiópia (Meseret; Ketema e Kassahun, 2020), Nigéria (Nkeiruka, Ebere & Obianime, 2012;Onyele & Anyanwu, 2018) e Argélia (Messaoudi & Begaa, 2018), em países Europeus, como Moldávia (Zinicovscaia et al, 2020) e Espanha (Martín-Domingo et al, 2017), em países do Oriente Médio, como Jordânia (Ababneh, 2017), Arábia Saudita (Ibrahim, 2014;Brima, 2017) e Irã (Zinsaz et al, 2015;Kohzadi et al, 2019) e em países da América do Sul, como o Brasil (Caldas & Machado, 2004;Leal et al, 2013;Silva, Francisconi & Gonçalves, 2016;Caldeirão et al, 2021;Souza et al, 2021;Tschinkel et al, 2020) e Peru (Zárate-Quiñones et al, 2021). Mas ainda há muito o que ser estudado (Zárate-Quiñones et al, 2021), considerando a importância dos oligoelementos para o metabolismo humano, bem como os riscos inerentes à saúde humana (Silva, Francisconi & Gonçalves, 2016).…”
Section: Metais Pesados Em Plantas Medicinais: Potencial Risco à Saúde Humanaunclassified